2017
DOI: 10.3390/met7070255
|View full text |Cite
|
Sign up to set email alerts
|

Failure Assessment of Steel/CFRP Double Strap Joints

Abstract: In the current study, the failure behavior of retrofitted steel structures was studied experimentally and theoretically with steel/carbon fiber reinforced polymer (CFRP) double strap joints (DSJs) under quasi-static tensile loading. A series of DSJs with different bonding lengths are also considered and examined to experimentally assess the effective bond length. To predict the failure load values of the tested specimens, a new stress-based method, namely the point stress (PS) method is proposed. Although some… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Their application together with FRP strengthening on stiff elements (reinforced concrete beams, stiff steel beams, or columns) is justified and effective [12], because joined components have low elongation limits, and, thus, they tolerate the use of adhesives with low deformability. The same situation (with positive results) applies to the use of an epoxy to strengthen a thin metal profile on a relatively short length, where the deformability of the adhesive is of lesser importance [13].…”
Section: Introductionmentioning
confidence: 95%
“…Their application together with FRP strengthening on stiff elements (reinforced concrete beams, stiff steel beams, or columns) is justified and effective [12], because joined components have low elongation limits, and, thus, they tolerate the use of adhesives with low deformability. The same situation (with positive results) applies to the use of an epoxy to strengthen a thin metal profile on a relatively short length, where the deformability of the adhesive is of lesser importance [13].…”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, in some researches dealing with experiments on steel/CFRP DSJs, complicated numerical were applied to the FE analyses. For instance, it can be referred to three researches [16,32,33]. According to the mentioned discussions, it can be expressed that if one of the failure model succeeded with high performance in predicting the failure loads values of the tested DSJs does not delivered this message that other failure models could not be utilized and developed.…”
Section: Limitations and Advantages Of The Cns Criterion For Dsjsmentioning
confidence: 99%
“…The failure assessment of double strap joints made with steel and CFRP was performed by Majidi et al, and by using a proposed approach (point stress method), the authors were able to predict the failure load under quasi‐static conditions, a method found to be in good agreement with experimental tests. More recently, Razavi et al presented a strain‐based criterion to predict the failure load of the same type of joints (based on a two‐dimensional linear elastic finite element analysis), being able to present a good consistency in its predictions and comparing well with experimental results found in the literature.…”
Section: Introductionmentioning
confidence: 99%